Bulk liquid membrane (BLM) for Cd(II) ions removal using trioctylamine (TOA) as carrier / Nur Athirah Azrai ... [et al.] - Azrai, Nur Athirah; Roseli, Effi Aidur Roza; Wahet, Farhana; Shah Buddin, Meor Muhammad Hafiz; Ahmad, Abdul Latif (2018)
The extraction of Cd(ll) ions by using bulk liquid membrane (BLM) was investigated in this current study. Similar to liquid extraction, BLM was used to enhance the process via Type II Facilitated Transpo1i. BLM consists of membrane phase which made up of carrier (Trioctylamine, TOA) dissolved in kerosene, feed phase CdCl2 dissolve in HCI solution and ammonia solution as the stripping phase. The aim of this study is to identify the condition for the ideal concentration of carrier (Trioctylamine) in the membrane phase as well as the stirring speed and extraction time. Experimental data obtained shows that the optimum conditions are; 0.1 wt% TOA in kerosene, 400 rpm and 4 hours. Extraction of Cd(I I) ions across BLM prefers acidic condition at pH of I. Maximum removal of Cd(Il) at 96.26% was achieved at this condition. The study was followed by determination of reaction rates (k1, k2) and flux (J) of Cd(II) extraction across BLM. lt was found that k1. k2 and J were 0.94 1,-1, 2.45 IY1 and 0.671 h·1 respectively